K. R. Bradley: Slaves and Masters in the Roman Empire. A Study in Social Control. Col. Latomus, vol. 185, Bruselas, 1984, 164 pp. - López Barja de Quiroga, Pedro (Gerión. Revista de Historia Antigua, 1987)
Sin resumen